A Study on Management Effectiveness of Farmer Producer Organizations in North-Eastern Karnataka - Karadipatil, Shweta; D.M. Chandargi; S. B. Goudappa (Journal of Agricultural Extension Management, 2022)
Farmer Producer Organizations in India help farmers in earning more returns through collective input purchase, collective marketing, processing, increasing productivity through procuring better inputs and augmenting the knowledge of farmers in managing their organization. An attempt was made to develop a standardized scale and analyze the management effectiveness of the selected FPOs. Management dimension analysis revealed that planning wise all the FPO members showed high agreement for effectively planning the activities (0.9 to 1.00). Similarly, all the FPOs members showed higher agreement (0.8 to 1.00) for communication, cooperation and coordination, commitment, leadership and decision making in FPOs. FPO members expressed medium levels (0.6 to 0.8) in organizing and control dimensions. Nisarga FPO was found to be the most effectively managed by its members among the five FPOs.